Morpho-molecular identification, pathogenicity for Piaractus mesopotamicus, and antimicrobial susceptibility of a virulent Flavobacterium columnare isolated from Nile tilapia cultured in Brazil - de Abreu Reis Ferreira, Daniel [UNESP]; Assane, Inácio Mateus [UNESP]; Vaneci-Silva, Daiane [UNESP]; do Vale Oliveira, André [UNESP]; Tamashiro, Geovana Dotta [UNESP]; Hashimoto, Diogo Teruo [UNESP]; Pilarski, Fabiana [UNESP] (My University, 2022)
Flavobacterium columnare is an important pathogen of freshwater fish that has severe impacts on the commercial aquaculture sector worldwide. In this study, we investigated the morpho-molecular characteristics, pathogenicity against pacu, Piaractus mesopotamicus, and antimicrobial susceptibility of a virulent F. columnare isolated from Nile tilapia cultured in Brazil. Diseased Nile tilapia having ulcerations on the skin were collected from a commercial fish farm located in Porto Ferreira, São Paulo, Brazil for the isolation of pathogenic bacteria. Isolates (n = 7) were identified by morphological, biochemical, and molecular analyses as F. columnare. Bacteria molecular characteristics were determined by restriction fragment length polymorphism (RFLP) using the restriction enzyme Hae III and phylogenetic analysis based on the partial sequence of the 16S rRNA gene. Susceptibility to enrofloxacin (ENRO), florfenicol (FFC), oxytetracycline (OTC), thiamphenicol (TAP), and their combinations were assessed by broth microdilution and chequerboard methods, respectively. The pathogenicity against pacu was analysed by experimental infection by immersion challenge with one of the clinical isolates (DV001, GeneBank Accession Number MW186708). The molecular analyses revealed that the clinical isolate belongs to F. columnare genetic group 4 and genomovar II and differs from strains previously isolated from cultured fish in Brazil. The clinical isolate was classified as wild-type for all tested antimicrobials, except for ENRO. Synergistic, additive, and antagonistic activities were reported when the combination of TAP and ENRO (ΣFIC = 0.5), FFC and TAP (ΣFIC = 0.75), and OTC and ENRO (ΣFIC = 3) were tested, respectively. The disease was reproduced in the experimental infection with F. columnare DV001 at 1 × 102, 1 × 104, and 1 × 105 colony-forming units (CFU) mL−1, and the cumulative mortality was 50%, 75%, and 87.5% within 15 days, respectively. The strain was highly virulent against pacu, and the LD50, LD90, and LD99 were established in 1.16 × 102, 4.6 × 104, and 1.8 × 107 CFU mL−1, respectively. This is the first report of F. columnare pathogenicity against pacu. Although the results of antimicrobial susceptibility testing suggest that available antimicrobials can be effective against the pathogen, the resistance against ENRO and pathogenicity against pacu has several implications. These findings will hopefully be useful in the development of effective vaccines and therapeutic strategies for the prevention and control of columnaris disease.
Keywords: Antimicrobial resistance; Bacterial infection; Flavobacterium columnare; Pathogenicity; Piaractus mesopotamicus; Restriction fragment length polymorphism